2013
DOI: 10.1155/2013/916253
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Repeated CT Scan Need in Blunt Head Trauma

Abstract: Background. Computed tomography (CT) is a vital tool in the workup of patients with closed head trauma. The aim of this study was to investigate the necessity of serial CT scans in patients with blunt head trauma. Methods. This is a retrospective study analyzing trauma patients between January and June 2012. Data were analysed by using frequencies, Kolmogorov-Smirnov (K-S), and Chi-square tests. Results. Of the total 351 control Head CTs, it was seen there were no different in 346 (98.6%). In CTs of another 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…Serkan Emre et al study showed that the first CT scan of head trauma patients in EDs are good guides for the status of patients with mild head trauma patients. Repeated CT scans after 6 hours of observation in ED room were not necessary if first CT was normal in most situations [16]. Whereas, this result was consistent with results of this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Serkan Emre et al study showed that the first CT scan of head trauma patients in EDs are good guides for the status of patients with mild head trauma patients. Repeated CT scans after 6 hours of observation in ED room were not necessary if first CT was normal in most situations [16]. Whereas, this result was consistent with results of this study.…”
Section: Discussionsupporting
confidence: 91%
“…Controversy exists as to the role of a routine repeat head Computed Tomography (CT) for patients with traumatic brain injury and an initially abnormal head CT. Brown CV et al reported that Patients with any head injury (mild, moderate, or severe) should undergo a repeat head CT after neurological deterioration, because it leads to intervention in over one-third of patients. Routine repeat head CT is indicated for patients with a GCS score ≤8, as results might lead to intervention without neurological change [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Performing a repeat head computed tomography (CT) after an initial negative head CT is one strategy to evaluate delayed intracranial hemorrhage. Evidence has shown that most DICHs occur within 6–24 h of injury [ 21 , 22 ], although a recent large multicenter prospective study found that delayed hemorrhages occurred up to 5 days after injury [ 19 ]. There is no clear consensus on whether or not to routinely perform repeat head CTs in elderly patients with minor injuries on ACAP therapies, although this is the standard practice in many European trauma centers [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This further highlights the importance of utilizing metrics, such as ECG or PPG waveform feature analysis, that are resilient to factors that impact the reliability of the GCS assessment. Serial CT imaging provides additional information regarding clinically silent progression of injury ( 37 39 ) with the aim of capturing signs of neurologic worsening which can lead to early medical and surgical interventions even before the clinical symptoms manifest ( 40 ). Despite our results indicating additional benefit of scoring severity of injury by CT imaging, a multicenter prospective study as well as several large single center cohort studies have failed to find factors that reliably predicted the correlation between ND and serial CT imaging ( 41 44 ).…”
Section: Discussionmentioning
confidence: 99%